UV–visible downshifting in CdWO4:Ce3+ nanosized phosphor. (December 2017) - Pawade, V.B.; Birmod, R.; Waghmare, Aishwarya; Dabre, K.V.; Dhoble, S.J.
Graphical abstract: Abstract: In this paper, the synthesis of Ce 3+ doped CdWO4 nanophosphor and its downshifting properties is presented. The reported nanosized phosphor was synthesized by low cost and low-temperature wet chemical method. Phase purity and crystallite size were measured by XRD and HRTEM techniques, and photoluminescence characterization was carried out for its downshifting properties. The XRD pattern reveals that the CdWO4 has a monoclinic structure and it is in good agreement with standard PDF pattern. HRTEM images reveal that the phosphor has nanoflakes and nanogranules structural morphology. The present phosphor CdWO4 :Ce 3+ shows good downshifting property and converts the broad ultraviolet band (ranging from 220 to 400 nm and peaking at 285 nm) into a visible spectral band extending from 400 to 650 nm and peaking at 474 nm. The excitation and emission spectra are analyzed by curve fitting using the Gaussian function for the contribution of the 5d-4f allowed the transition of Ce 3+ ion. Such downshifting phosphor may be used to improve the light conversion efficiency of Si solar cells.